Design of an Instrument to Evaluate Organizational Design Characteristics Based on the Organizational Configuration Model (2022)
The purpose of this article was to design and validate an instrument to determine relevant variables of the business environment, demeanor, and organizational behaviors linked to the Organizational Configuration Model and its relevance in these tumultuous times driven by the pandemic. From the literature, fifty-nine organizational attributes were extracted and administered to a random sample of 160 managers. Using a combined approach, i.e., exploratory factor analysis and construct validity, a structure of eight factors were extracted that explained 66.3 percent of the total variance with an exhibited satisfactory sample adequacy for the factor analysis (KMO = 0.63). An instrument was designed with these eight factors that provided a focused and valid perspective capable of assessing the impact and continued viability of a business’s organizational configuration under unsettled economic times. © Common Ground Research Networks, Ronald R. Rojas, Oriana Susana Martinez Palomino, Jorge Luis Villalba Acevedo, Alberto Emilio Gómez Torres, All Rights Reserved.